Intimate Partner Violence Survivors’ Housing Needs and Preferences: A Brief Report - Fraga Rizo, Cynthia (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) victimization contributes to homelessness and housing insecurity for survivors and their children. Despite growing interest in expanding strategies for addressing the housing needs of survivors, there is a dearth of knowledge regarding survivors’ preferences and recommendations. To begin to address knowledge gaps, this article reports findings from a qualitative study examining the housing needs of IPV survivors and survivors’ preferences and recommendations for addressing their housing needs. In-depth interviews with 19 adult IPV survivors in a southeastern community determined three key themes: (a) IPV housing needs and challenges, (b) domestic violence shelter strengths and concerns, and (c) recommendations for addressing survivors’ housing needs. The findings highlight the need for flexibility and variability in housing services as opposed to a one-size-fits-all strategy, and stress the importance of centering the voices of survivors as the field explores new housing directions.